Human SP-D Acts as an Innate Immune Surveillance Molecule Against Androgen-Responsive and Androgen-Resistant Prostate Cancer Cells - Thakur, Gargi; Prakash, Gagan; Murthy, Vedang; Sable, Nilesh; Menon, Santosh; Alrokayan, Salman H.; Khan, Haseeb A.; Murugaiah, Valarmathy; Bakshi, Ganesh; Kishore, Uday; Madan, Taruna (Frontiers in Oncology, 2019)
Surfactant Protein D (SP-D), a pattern recognition innate immune molecule, has been implicated in the immune surveillance against cancer. A recent report showed an association of decreased SP-D expression in human prostate adenocarcinoma with an increased Gleason score and severity. In the present study, the SP-D expression was evaluated in primary prostate epithelial cells (PrEC) and prostate cancer cell lines. LNCaP, an androgen dependent prostate cancer cell line, exhibited significantly lower mRNA and protein levels of SP-D than PrEC and the androgen independent cell lines (PC3 and DU145). A recombinant fragment of human SP-D, rfhSP-D, showed a dose and time dependent binding to prostate cancer cells via its carbohydrate recognition domain. This study, for the first time, provides evidence of significant and specific cell death of tumor cells in rfhSP-D treated explants as well as primary tumor cells isolated from tissue biopsies of metatstatic prostate cancer patients. Viability of PrEC was not altered by rfhSP-D. Treated LNCaP (p53+/+) and PC3 (p53 −/−) cells exhibited reduced cell viability in a dose and time dependent manner and were arrested in G2/M and G1/G0 phase of the cell cycle, respectively. rfhSP-D treated LNCaP cells showed a significant upregulation of p53 whereas a significant downregulation of pAkt was observed in both PC3 and LNCaP cell lines. The rfhSP-D-induced apoptosis signaling cascade involved upregulation of Bax:Bcl2 ratio, cytochrome c and cleaved products of caspase 7. The study concludes that rfhSP-D induces apoptosis in prostate tumor explants as well as in androgen dependent and independent prostate cancer cells via p53 and pAkt pathways.